Genetic Tuning of Iron Oxide Nanoparticle Size, Shape, and Surface Properties in Magnetospirillum magneticum. (14th October 2020) - Furubayashi, Maiko; Wallace, Andrea K.; González, Lina M.; Jahnke, Justin P.; Hanrahan, Brendan M.; Payne, Alexis L.; Stratis‐Cullum, Dimitra N.; Gray, Matthew T.; Liu, Han; Rhoads, Melissa K.; Voigt, Christopher A.
Abstract: Different applications require iron oxide nanoparticles (IONPs) of varying size, shape, crystallinity, and surfaces that can be controlled through the synthesis reaction conditions. Under ambient conditions, Magnetospirillum magneticum AMB‐1 builds uniform Fe3 O4 IONPs with shapes and crystal forms difficult to achieve with chemical synthesis. Genetic engineering can be used to change their properties, but there are few tools to fine‐tune expression over a wide range. To this end, ribosome binding sites, minimal constitutive promoters, and inducible systems (IPTG, aTc, and OC6) with large dynamic range are designed. These are used to control M. magneticum genes that affect IONP properties, including size ( mamC ), morphology ( mms6 ), chain length ( mamK ), and surface coating ( mamC fusions). These systems increase the fraction of IONPs that are less than 30 nm, produce rounded particles, and lead to the production of intracellular chains with 24 or more IONPs. In addition, the R5 peptide from diatoms is found to silica coat the surface of metal oxide nanoparticles (Fe, Ti, Ta, Hf) and can be genetically directed to the IONP surface. This work demonstrates the genetic control of IONP properties, but also highlights the robustness of the system, which complicates genetic engineering to produce radically different particles and structures. Abstract : Magnetospirillum magneticum builds uniform Fe3 O4 iron oxide nanoparticles (IONPs) with shapes and crystal forms difficult to achieve with chemical synthesis. Here, genetic control of IONP properties is demonstrated by controlling the expression of M. magneticum genes that affect IONP properties, including size, morphology, chain length, and surface coating.